The implementation of pela gandong cultural values in fostering harmonious community living in maluku from the perspective of the qur'an - R Def Mochtar Hassanusi (12 Waiheru, 2023)
This article was compiled to describe the implementation of the Pela Gandong Cultural values ​​in Fostering Harmonious Community Life in Maluku from the Perspective of the Qur'an. The method used in this research is a literature study. Therefore, to answer the research questions, a literature study approach is carried out related to the research question. The results of the study conducted, obtained information on a number of things, including: there are four cultural values ​​of Pela Gandong in fostering harmony in community life in Maluku based on the perspective of the Koran, including equality of human dignity, tabayyun, moderation, and the rule of law.